Constitutional Values in Education: The Judiciary’s Interpretive Role - Baheti, Ashok; Mukundarajan, S (International Journal of Advanced Research in Peace, Harmony and Education; Vol 10 No 1 (2025): International Journal of Advance Research in Peace, Harmony and Education, 2025)
Education is a fundamental pillar in upholding constitutional values such as justice, liberty, equality, and fraternity. The judiciary plays a pivotal role in interpreting constitutional provisions and ensuring their implementation in educational policies and governance. Through landmark judgments, the courts have expanded the scope of the right to education, reinforced inclusivity, and upheld the principles of equity and social justice. The judiciary has been instrumental in shaping affirmative action policies, protecting minority educational rights, and addressing issues of discrimination and accessibility in education. Cases like Unnikrishnan v. State of Andhra Pradesh (1993) and Mohini Jain v. State of Karnataka (1992) have significantly influenced the recognition of education as a fundamental right. Additionally, judicial interventions have safeguarded the autonomy of minority institutions under Articles 29 and 30 while promoting equitable access to education for marginalized communities. However, challenges remain in the enforcement of judicial directives, requiring a collaborative approach among policymakers, educators, and legal institutions. Strengthening legal frameworks and ensuring effective implementation of court rulings can help bridge gaps in access and quality. This paper explores the judiciary’s role in reinforcing constitutional values in education, advocating for an inclusive and just educational framework.